Downstream Process of Technology Invention Products to the Market - Bambang S Pujantiyo (Jurnal Manajemen dan Kewirausahaan, 2022)
A Triple Helix collaboration between Academician Businesses Government (ABG), is one of the keys to success in the downstream process of invention of technology-based research results so that they can be commercialized into business products. This downstream process is based on the Randal Goldsmith model which consists of 3 stages: investigation,  development/validation, commercialization. In Indonesia, this downstream process has been carried out a lot, but it has not produced many significant business products. The purpose of this study is to improve the model, especially at the validation stage, including production tests, market tests, and sales tests. After the improvement of the model was implemented in several institutions, it was found that more inventions of research results could be used as business products compared to before. With these results, it can be concluded that the improvement of the model can be used nationally to be able to support the national income.